Implementation of the Explicit Instruction Model Using the Storytelling Method Based on Reading Short Stories for Fifth Grade Elementary School Students State 116241 Kampung Baru Rantau Prapat - Wati Ritonga, Noprida; Rahmat Kartolo (International Journal of Educational Research Excellence (IJERE), 2026)
The problem in this study is how the storytelling method based on reading short stories through the explicit instruction model influences fifth-grade elementary school students. Negeri 116241 Kampung Baru Rantau Prapat Academic Year 2024-2025. This study aimed to determine the effect of the storytelling method based on reading short stories through an explicit instruction model on fifth-grade elementary school students. State 116241 Kampung Baru Rantau Prapat Academic Year 2024-2025. The participants of this study were fifth-grade elementary school students. Negeri 116241 Kampung Baru Rantau Prapat in the 2024-2025 academic year, totaling 40 students. The results showed that students who previously did not understand and were less active in the learning process became more active. The students were able to construct their understanding through groups and individuals from the learning material. Students were more independent and creative because the explicit instruction model learning provided them with full opportunities to plan and work on their assignments and were appreciated in the performance process. The storytelling method was based on reading short stories of fifth-grade elementary school students. Negeri 116241 Kampung Baru Rantau Prapat in the 2024-2025 Academic Year using the explicit instruction model showed an average value of 75.00 while the conventional model was 67.411. This proves that there was a positive influence on the application of the explicit instruction model.